The association between bone turnover biomarkers and the severity of white matter hyperintensities - You, Qian; Li, Ying; Ge, Yufeng; You, Xiaofan; Chen, Xufeng; Lei, Lin; Hu, Hongtao (Frontiers in Neurology, 2025)
BackgroundBone health may be associated with cerebral small vessel disease. This study aims to explore the correlation between bone turnover biomarkers (BTMs) and parathyroid hormone (PTH) with the severity of white matter hyperintensities (WMH).Materials and methodsWe retrospectively analyzed 213 inpatients from the Neurology Department of Beijing Jishuitan Hospital between June 2021 and May 2022. The WMH burden was assessed semi-quantitatively using the age-related white matter changes scale and the Fazekas scale, with the latter separately evaluating periventricular WMH (PWMH) and deep WMH (DWMH). Participants were categorized into two groups based on WMH severity. Binary logistic regression was performed to investigate the relationship, and subgroup analyses were conducted across subgroups stratified by sex, hypertension, and diabetes.ResultsPatients with severe WMH, PWMH, and DWMH had significantly higher β-carboxy-terminal cross-linked telopeptide of type 1 collagen (β-CTX) and PTH levels compared to those in the mild groups. After adjusting for confounding factors, elevated β-CTX levels remained associated with severe WMH (OR: 4.44, 95% CI: 1.33–14.81) and severe PWMH (OR: 6.37, 95% CI: 1.80–22.47), while increased PTH levels were associated with severe DWMH (OR: 1.02, 95% CI: 1.01–1.05). Subgroup analysis showed a significant relationship between PTH and the severity of WMH and PWMH in patients with diabetes (p for interaction < 0.05).Conclusionβ-CTX was independently linked to WMH/PWMH severity, and PTH to DWMH severity, pointing to a possible bone–cerebrovascular axis. Larger prospective and interventional studies should confirm these markers as potential CSVD biomarkers and treatment targets.